PENERAPAN METODE CFC (CONTINUOUS FLOW CASTING) PADA PERBAIKAN KOMPONEN YANG TERBUAT DARI PADUAN ALUMINIUM - Muki Satya Permana; Edho Prakoso; Muhammad Iqbal Taufani (Jurnal Ilmiah Teknik Mesin POROS, 2018)
Abstract: Many automotive components are made of Aluminum alloy. The broken or cracked components are generally replaced with a new product. For the reason of the number of component and cost, recondition is considered as a very profitable solution. So far, the recondition on this alloy component was repaired by using TIG or MIG. However, this alloy is easily oxidized and forms Aluminum oxide. In addition, the alloy is also easy to form a fine cavity and weld cracking. So, the problem to be solved in this work is how to conduct the CFC (Continuous Flow Casting) process so that the repair process produces a joining that is free from cavities and hot cracks. In this work, the objective is to repair an aluminum alloy by using the CFC method. The problem solution is performed by experimental investigation, which is the repair process using CFCs. The surface repairs result was poured by dye penetrant fluid then metallographic examination and hardness testing. From the experimental results obtained that the metallurgical bonding in the connection area is considered good because there is continuity of micro structure between the parent metal and filler metal.